2021
DOI: 10.1007/s00134-021-06594-w
|View full text |Cite
|
Sign up to set email alerts
|

Can serum markers of brain injury predict good neurological outcome after out‑of‑hospital cardiac arrest?

Abstract: We recently read the article by Marion Moseby-Knappe et al. published in Intensive Care Medicine [1]. The authors suggested that "low levels of brain injury markers in blood are associated with good neurological outcome after cardiac arrest (CA). " Their study provided the predictive value of clinically available markers on the prognosis of patients with postarrest within the Target Temperature Management after out-of-hospital cardiac arrest (TTM) trial. The findings of this study are potentially valuable in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We are grateful for the interest in our study shown by Li and Wang who raise concerns about the methods used and interpretation of results [1].…”
mentioning
confidence: 99%
“…We are grateful for the interest in our study shown by Li and Wang who raise concerns about the methods used and interpretation of results [1].…”
mentioning
confidence: 99%